Penguatan Budaya Keselamatan Laboratorium melalui Pelatihan K3 bagi Siswa SMA IT Insan Mulia Boarding School Pringsewu - Idra Herlina; Cindy Moyna Clara L.A.; Demi Dama Yanti; Mariyam Mariyam; M. Alvien Ghifari; Ahmad Anggraria Jaya Agung; M. Luqmanul Hakim Habibie (CV. SINAR HOWUHOWU, 2026)
School laboratories are essential for developing science process skills; however, their use must be accompanied by consistent occupational safety and health practices. This community service program aimed to improve students’ understanding and awareness of laboratory safety culture at SMA IT Insan Mulia Boarding School Pringsewu. The program involved coordination with the partner school, preparation of training materials and evaluation instruments, and an interactive training session on 14 April 2026. The materials covered basic laboratory safety, the 5R principles, hazard identification, simple risk assessment, and appropriate use of personal protective equipment. Evaluation was conducted descriptively by comparing the mean pre-test and post-test scores and observing participant engagement. The mean score increased from 86.60 to 90.50, representing a 3.90-point or 4.50% improvement. Participants also engaged actively in case discussions and demonstrated a better understanding of safe work behaviour. The school’s support in providing the venue, participants, and documentation strengthened implementation. The training offers an initial foundation for integrating safe working habits into routine school laboratory activities.